Analysis of the influence of socioeconomic factors on women's decision to work in the formal-informal sector in east Lombok Regency - Handayani, Tuti; Wijimulawiani, Baiq Saripta (Institute of Computer Science (IOCS), 2024)
This study analyzes the influence of socioeconomic factors on women's decisions in East Lombok Regency to work in the formal or informal sector. With a quantitative approach and logistic regression methods, data were collected from 908 respondents registered in the National Labor Force Survey. The results show that education, income, and working hours significantly affect women's choice of job sectors. Lower education increases the chances of choosing the informal sector, while the increase in working hours is related to the tendency to work in the informal sector. Although income has a significant impact, its influence on sectoral decisions is not as large as education and working hours. These findings can be a reference for policymakers in designing more effective women's empowerment programs.